2003 IEEE International Conference on Robotics and Automation (Cat. No.03CH37422)
DOI: 10.1109/robot.2003.1241744
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of grasping by using a required external force set

Abstract: In this paper, we consider an optimization of grasping by using a required external force set. By using the set, we can not only deal with whatever a desired grasp is, such as force closure or equilibrium grasp, but also evaluate the magnitudes of the resistible external forces and moments. Then, we define an optimization problem from the viewpoint of decreasing the magnitudes of the contact forces required to resist the required external force, and show that we can solve the problem by using a branch-and-boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
(1 reference statement)
0
33
0
Order By: Relevance
“…This indicates that the normal way of grasping by increasing the pressure on the object does not work well for grasping a sheet. Conventional grasping methods (for example, see [17], [18]) may not work for sheet grasping. In the comparison of the theoretical and experimental results, the theoretical results were close to the experimental results.…”
Section: Comparison Between Theory and Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that the normal way of grasping by increasing the pressure on the object does not work well for grasping a sheet. Conventional grasping methods (for example, see [17], [18]) may not work for sheet grasping. In the comparison of the theoretical and experimental results, the theoretical results were close to the experimental results.…”
Section: Comparison Between Theory and Experimental Resultsmentioning
confidence: 99%
“…In sum, various levels of softness for the fingertips have both merits and demerits, and the type of fingertip should be selected according to the task. The conventional metric evaluating grasping (for example, see [17], [18]) evaluates based on convex theory. Therefore, if the magnitude of grasping forces was set to be twice, the magnitude of resistible force also got to be twice, irrespective of stiffness of fingertips.…”
Section: B Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding an optimal grasp is e.g. reported by Watanabe et al [108]. Mishra [78] shows that in a planar case an optimal three finger grasp can can be computed efficiently.…”
Section: Grasp Planningmentioning
confidence: 99%
“…Garg and Dutta [28] shown that the internal forces required for grasping deformable objects vary with size of object and finger contact angle. In [29], Watanabe and Yoshikawa investigated optimal contact points on an arbitrary shaped object in 3D using the concept of required external force set. Ding et al proposed an algorithm for computing form closure grasp on a 3D polyhedral object using local search strategy in [30].…”
Section: Issues and Prior Researchmentioning
confidence: 99%